The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1996
DOI: 10.1126/science.273.5283.1853
|View full text |Cite
|
Sign up to set email alerts
|

Initiation of Runaway Cell Death in an Arabidopsis Mutant by Extracellular Superoxide

Abstract: Reactive oxygen intermediates (ROIs) regulate apoptosis during normal development and disease in animals. ROIs are also implicated in hypersensitive resistance responses of plants against pathogens. Arabidopsis lsd1 mutants exhibited impaired control of cell death in the absence of pathogen and could not control the spread of cell death once it was initiated. Superoxide was necessary and sufficient to initiate lesion formation; it accumulated before the onset of cell death and subsequently in live cells adjace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

22
591
0
3

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 817 publications
(631 citation statements)
references
References 44 publications
22
591
0
3
Order By: Relevance
“…Yellow, water-soluble NBT is reduced by superoxide radicals to blue, water-insoluble formazan (Grosskinsky et al, 2012;Jabs et al, 1996;Kawarazaki et al, 2013;L'Haridon et al, 2011;Liao et al, 2012;Wang and Higgins, 2006;Xia et al, 2009). Superoxide anion radicals can also be detected using dihydroethidium (DHE), a cell-permeable blue fluorescent stain that forms red fluorescent oxyethidium upon oxidation and intercalates with nucleic acids (see recent applications in Lehotai et al, 2011;Mai et al, 2013;Pet} o et al, 2013).…”
Section: Detection Of Rosmentioning
confidence: 99%
“…Yellow, water-soluble NBT is reduced by superoxide radicals to blue, water-insoluble formazan (Grosskinsky et al, 2012;Jabs et al, 1996;Kawarazaki et al, 2013;L'Haridon et al, 2011;Liao et al, 2012;Wang and Higgins, 2006;Xia et al, 2009). Superoxide anion radicals can also be detected using dihydroethidium (DHE), a cell-permeable blue fluorescent stain that forms red fluorescent oxyethidium upon oxidation and intercalates with nucleic acids (see recent applications in Lehotai et al, 2011;Mai et al, 2013;Pet} o et al, 2013).…”
Section: Detection Of Rosmentioning
confidence: 99%
“…HR, a form of programmed cell death (PCD) occurs as a plant immune response to survive pathogen attack [55]. Dat et al [54] and Jabs et al [56] identified H 2 O 2 and superoxide anion as initiators of PCD events and necrotic lesion formation, respectively. There is increasing evidence that various concentrations and durations of ROS exposure will lead to either necrosis or PCD [57] and [58].…”
Section: Asa Treatmentmentioning
confidence: 99%
“…The oat blight disease induced by the toxin victorin involves the specific cleavage of ribulose-1,5-bisphosphate carboxylase/oxygenase and may interact with senescence mechanisms (Navarre and Wolpert, 1999). The types and number of pathways, whether they are activated separately or have cross-talk, and how they converge to result in the similar cell morphology and ultimately cell death are still unknown.The generation of reactive oxygen species (ROS) has been suggested as a key trigger or mediator to PCD accompanying the HR (Jabs et al, 1996;May et al, 1996;Mittler et al, 1996; Bestwick et al, 1997;Lamb and Dixon, 1997; Desikan et al, 1998). Hydrogen peroxide also accumulates in lettuce leaf tracheary elements (Bestwick et al, 1997) and senescing pea leaves (Pastori and del Río, 1997).…”
mentioning
confidence: 99%
“…Hydrogen peroxide also accumulates in lettuce leaf tracheary elements (Bestwick et al, 1997) and senescing pea leaves (Pastori and del Río, 1997). Thus, ROS might be a general trigger for PCD in plants, although they may be insufficient to induce PCD (Glazener et al, 1996).Here, hydrogen peroxide correlated closely with the D4-satRNA-induced rapid cell death (data not shown), which suggests the possibility of a common pathway for hydrogen peroxide to induce host cell death during both the incompatible and susceptible reactions.The accumulation of hydrogen peroxide involves the activation of a plasma membrane-associated NAD(P)H oxidase (Jabs et al, 1996) and the inhibition of catalase expression and suppression of cytosolic ascorbate peroxidase during the response of plants to pathogens (Chamnongpol et al, 1996;Takahashi et al, 1997;Mittler et al, 1998). Recently, cysteine proteases were found to be activated by oxidative stress in soybean cells and inhibition of cysteine proteases could block PCD (Solomon et al, 1999).…”
mentioning
confidence: 99%
See 1 more Smart Citation